Al Ashil dan Al Dakhil (Studi Kasus Penafsiran Syaiful Karim Terhadap QS. Al Baqarah Ayat 186 (ayat Tentang Doa Pada Channel Youtube Syaiful Karim) - Sevanura, Firdausa; Safitri, Wangi Firdaus (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
The phenomenon of interpretive deviation (ad-dakhil) remains prevalent, especially across social media content. This is evident in the presence of certain preachers who frequently appear in their social media posts. Specifically, in Syaiful Karim's YouTube content, he tends to interpret the Qur'an based on his own rational thinking. This results in a lack of proper foundational references, weak arguments, and a loss of authenticity in the interpretation of the Qur’an. This article analyzes the concepts of al-ashil (authentic interpretation) and ad-dakhil (deviated interpretation) in Syaiful Karim’s YouTube explanation of Surah Al-Baqarah verse 186 (a verse about prayer). The aim of this study is to examine the presence of ad-dakhil in his interpretation of the verse and to identify the factors contributing to this deviation. The research is a library study, using observation as the primary method to collect data from phenomena, locations, objects, and recorded videos. The results show that ad-dakhil is present in Syaiful Karim’s video when interpreting Surah Al-Baqarah verse 186, particularly in the form of distorted rational reasoning (ad-dakhil bi al-ra’yi) that diverges from the proper interpretive guidelines (al-ashil). The primary factor contributing to this is his textual return to the literal meaning of words, followed by a rational reinterpretation based on his personal understanding.